Crossing Borders with Satyrs, the Irrepressible Genre-Benders of Pastoral Tragicomedy. (1st September 2020) - Nicholson, Eric
ABSTRACT: Although the ancient Athenian satyr-play was the model for Italian Renaissance pastoral tragicomedy, its chorus of singing and dancing satyrs was suppressed, and these same essential characters were often reduced to a solitary outsider figure representing a violent threat rather than a regenerative force for human communities. My essay asks how and why this reduction became a prevalent dramatic choice, as well as how and why the genre-bending spirit of satyrs nevertheless persisted, with distinct modulations, in many Italian and English plays. Historiographical and theoretical insights from the field of animal studies shape my comparative analysis: these include Donna Haraway's pluralistic and playfully companionate models of 'natureculture' and respect. A key focus is on tensions between anthropocentric and theriophilic attitudes – also expressed through the figure of the 'Wild-Man' – and how they inform pastoral productions from Giraldi Cinzio's Egle to Shakespeare's Winter's Tale, revealing the protean vitality of buffoonish, irrepressibly theatrical satyrs.